From scandal to style - Knothe, Jacek (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
It is assumed, that the architecture of the ‘Age of Promotorism’, commonly called Grűnderzeit, was omnipresent in Germany in the years 1870-1920, i.e. longer than till the end of 1st World War, being the turning point of the 20th century. In Poland, Grűnderzeit style followed with only a small delay the influx and spread of technical progress and inventions from Germany. Dwellings of that time, commonly present in most Polish town centers, despite heavy demolition caused by the II World War, still constitute the oldest and most valuable part of town fabric, and are being considered the esthetic canon of historical multifamily housing relic. It is the intention of the author to deconstruct the term of ‘historism’ commonly used in Polish literature for practically any architectural form dating prior to modernism, isolating thereof the term of ‘Grűnderzeit’, and to reintroduce the meaning of Grűnderzeit as a more accurate term, based on historical background of 19th century Europe. It is also the aim to end the myths and the prejudice against the style of ‘Grűnderzeit’ viewed as unwelcomed German influence. An ungrounded belief, that the XIX century architecture in Poland had no roots in 19th century German architecture, has no reason and ground in the era of globalism.